DEVELOPMENT OF A MATHEMATICAL MODEL FOR MAXIMIZING ECONOMIC RETURNS IN SMALL-SCALE AGRICULTURAL UNITS - André Sandmann; Ana Flavia M. T. Sandmann; José A. A. dos Santos; Fabiana C. A. Schutz; Lidinalva R. dos Santos; Fernando L. Precoma (Engenharia Agrícola)
ABSTRACT In this study, we developed a mathematical model to maximize economic returns in small-scale agricultural production units. The study was conducted on a rural property in Medianeira, Paraná, Brazil, dedicated to producing animal protein, grains, and silage. Production dynamics were analyzed through interviews and cost estimates, gathering technical, economic, and financial coefficients for model formulation. Using LINGO software, we performed economic calculations and defined technical, financial, and environmental constraints. The model proved effective in maximizing biennial economic returns and efficiently utilizing the available area and generated waste. The results showed that mathematical modeling is a valuable tool for developing and managing agricultural activities, enhancing sustainability, and enabling informed decision-making in high-impact environmental contexts.